2017
DOI: 10.1038/s41598-017-16147-1
|View full text |Cite
|
Sign up to set email alerts
|

T helper cells with specificity for an antigen in cardiomyocytes promote pressure overload-induced progression from hypertrophy to heart failure

Abstract: We investigated whether CD4+-T cells with specificity for an antigen in cardiomyocytes promote the progression from hypertrophy to heart failure in mice with increased pressure load due to transverse aortic constriction (TAC). OT-II mice expressing a transgenic T cell receptor (TCR) with specificity for ovalbumin (OVA) on CD4+-T cells and cMy-mOVA mice expressing OVA on cardiomyocytes were crossed. The resulting cMy-mOVA-OT-II mice did not display signs of spontaneous autoimmunity despite the fact that their O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 60 publications
(104 reference statements)
1
33
0
Order By: Relevance
“…For Transverse aortic constriction (TAC) female mice of an age between 8 and 12 weeks were used for experiments. TAC was performed by surgical placement of a suture around the transverse aorta sized to a 26G needle, as described previously ( Gröschel et al., 2017 ). Mice were subjected either to TAC or a sham operation.…”
Section: Methodsmentioning
confidence: 99%
“…For Transverse aortic constriction (TAC) female mice of an age between 8 and 12 weeks were used for experiments. TAC was performed by surgical placement of a suture around the transverse aorta sized to a 26G needle, as described previously ( Gröschel et al., 2017 ). Mice were subjected either to TAC or a sham operation.…”
Section: Methodsmentioning
confidence: 99%
“…TAC and sham surgery was performed as described previously ( 12 , 16 ). Briefly, the mice received intraperitoneal injections of medetomidin (0.5 mg/kg), midazolam (5 mg/kg), and fentanyl (0.05 mg/kg) for anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that T helper cells with specificity for an antigen in cardiomyocytes can contribute to the progression of heart failure after TAC also independently of autoantibodies ( 12 ). For this purpose, cMy-mOVA mice expressing the model antigen ovalbumin (OVA) on cardiomyocytes ( 13 ) were crossed with OT-II mice ( 14 ) expressing a transgenic T cell receptor (TCR) on CD4 + -T cells with specificity for OVA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 When ovalbumin peptide is exclusively expressed on cardiomyocytes, cardiac inflammation is partially restored, suggesting that T-cell activation with ovalbumin peptide can mediate some pathology, but other signals are required to progress to HF. 57 Although IFN-g is profibrotic, IL-10 is antifibrotic, in TAC. 54,58 The mechanisms of immune cell trafficking to the heart in response to cardiac pressure overload are starting to be unveiled.…”
Section: Pressure Overloadeinduced Hfmentioning
confidence: 99%